1961
DOI: 10.1021/ja01467a007
|View full text |Cite
|
Sign up to set email alerts
|

A Metal Carbonyl Compound of Titanium1

Abstract: Anal. Calcd. for [Co(C2H8NZ)2C~O4]C1~Hz0: C, 22.48; H,5.66; N, 17.48. Found: C,22.70; H, 5.76; N, 17.69. d-Oxalatobisethylenediamine-cobalt(II1)Iodide .-The dl-chloride, above, (12.84 9.) in water (80 ml., 65"), was shaken with silver acetate (6.4 g.) for 10 min. The silver chloride was removed and washed with hot water. To the filtrate a t 60' was added l-K[CoEDTA].2Hz0 (8.44 8.) and dissolved by shaking. Almost immediately the diastereoisomer d-[CoenzCz04]-Z-[Co(EDTA)]~ 3Hz0 commenced t o separate, and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Carlo Floriani had previously shown that vanadocene monocarbonyl underwent reductive cleavage by Na metal under a CO atmosphere to give good yields of CpV(CO) 4 (eq 19) We wondered whether titanocene dicarbonyl, the first known group 4 carbonyl, would undergo an analogous reduction because no previous attempts to reduce this species had been reported. It proved to be inert under Floriani conditions (eq 19), but the addition of naphthalene afforded [CpTi(CO) 4 ] - , albeit in only 20% (unoptimized) isolated yields.…”
Section: Zerovalent and Lower-valent Carbonyls Of Ti Zr And Hfmentioning
confidence: 99%
“…Carlo Floriani had previously shown that vanadocene monocarbonyl underwent reductive cleavage by Na metal under a CO atmosphere to give good yields of CpV(CO) 4 (eq 19) We wondered whether titanocene dicarbonyl, the first known group 4 carbonyl, would undergo an analogous reduction because no previous attempts to reduce this species had been reported. It proved to be inert under Floriani conditions (eq 19), but the addition of naphthalene afforded [CpTi(CO) 4 ] - , albeit in only 20% (unoptimized) isolated yields.…”
Section: Zerovalent and Lower-valent Carbonyls Of Ti Zr And Hfmentioning
confidence: 99%
“…This species was tentatively identified as ''CpTi(CO) 4 I" [16], on the basis of its reaction with Na + C 5 H 5 À , which gave small amounts of the prototypical titanium carbonyl complex [Cp 2 Ti(CO) 2 ] [23]:…”
Section: Syntheses Of 1-4mentioning
confidence: 99%
“…As part of our continuing joint program on the formation and structure of organometallic products derived from metal carbonyls and acetylenes, we report herein on the reaction of 1 and hexafluoro-2-butyne, as well as on the results of a single-crystal X-ray crystallographic study which together with spectral measurements fully characterize the organometallic product produced as a novel titanoxane (4). butyne would lead either to a titanole (2) or to an r;2-acetylene complex (3),10 in analogy with earlier reported reactions of 1 with diphenylacetylene.8,9 Accordingly, 1 was allowed to react with an excess of hexafluoro-2-butyne in benzene solution at 55 °C in a sealed system for 16 h. Chromatography of the dark orange reaction mixture on silica gel under argon produced an orange solid, which upon crystallization from tolu-(10) Formation of a product such as 3 would be less likely under our reaction conditions, since the analogous diphenylacetylene complex was produced only under conditions in which carbon monoxide was removed as it formed.…”
mentioning
confidence: 99%